2008
DOI: 10.2172/946673
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Juvenile Chinook Salmon Passing the Bonneville Dam Spillway in 2007

Abstract: Executive SummaryIn 2007, the Portland District of the U.S. Army Corps of Engineers contracted with the Pacific Northwest National Laboratory (PNNL) to conduct an acoustic telemetry study to estimate the survival of juvenile Chinook salmon passing the spillway at Bonneville Dam. Fish longer than 95 mm were surgically implanted with Juvenile Acoustic Telemetry System (JSATS) and passive integrated transponder (PIT) tags, held overnight in tanks supplied with continuous flow of river water to allow time for reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Observing slower egress rates for FC through middle spill bays (Point 6 above) is consistent with findings in 2007. In 2007 found that the mean travel time from spillway passage to an egress array located 9 km downstream of the dam was 20 minutes longer (P = 0.0105) for fish passing 4.5 through middle bays (2.58 hours) than it was for fish passing through end bays (2.26 hours).…”
Section: Egress Ratessupporting
confidence: 86%
See 1 more Smart Citation
“…Observing slower egress rates for FC through middle spill bays (Point 6 above) is consistent with findings in 2007. In 2007 found that the mean travel time from spillway passage to an egress array located 9 km downstream of the dam was 20 minutes longer (P = 0.0105) for fish passing 4.5 through middle bays (2.58 hours) than it was for fish passing through end bays (2.26 hours).…”
Section: Egress Ratessupporting
confidence: 86%
“…Previous experience indicates that dead fish usually travel much slower than live fish because they typically sink for a few days before they float and travel at the speed of prevailing river currents (Counihan et al 2006a(Counihan et al , 2006bPloskey et al 2008). The tendency of dead fish to travel slower than live fish led Counihan et al (2006a) to exclude data for fish with long egress times (>99.7 percentile) from survival calculations.…”
Section: Effect Of Detecting a Dead Tagged Fish On Survival-detectionmentioning
confidence: 99%
“…In 2006, the JSATS receivers were deployed at various locations between John Day Dam and Camas, Washington (a 150-km reach of the river), to estimate turbine passage and tailwater survival rates at John Day Dam, and dam-passage and tailwater-passage survival rates for The Dalles Dam and Bonneville Dam (Ploskey et al 2007). The first deployment of the JSATS cabled system was in 2007 at the Bonneville spillway to estimate route-specific passage and survival rates (Ploskey et al 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Several filtering algorithms were then applied to the raw results from the decoding utilities to exclude spurious data and false positives. Tag-detection data from JSATS autonomous nodes were processed by two independent groups as a quality-control measure as in previous studies (Ploskey et al 2007;Ploskey et al 2008) using standardized methods. One method processed data using programs written in Python, and the other involved processing data with programs written in the Statistical Analysis System (SAS).…”
Section: Signal Decoding and Filteringmentioning
confidence: 99%
See 1 more Smart Citation